Effect of Circuit-Based Strength-Endurance Training on Biomechanics and 800m Performance in Junior Female Athletes - Kadhem Hassoon, Essam (Pubmedia Jurnal Pendidikan Olahraga, 2025)
The purpose of this study was to examine the impact of long-term circuit strength-endurance training in running on selected biomechanical variables and performance in women 800 m young runners. Eight weeks with two sessions per week were applied to a sample of five athletes of the National Talent Center in Athletics in training exercises to the muscles which play a role in running. Running speed, step length, step frequency, lap time and total 800-m performance were assessed during both pre- and post-test after a series of video and biomechanical analysis tests. Results demonstrated significant enhancements at lap levels including running speed for all laps, step length, lap time, and total race time (p < 0.05). It is concluded that the utilized training program results in muscular endurance and biomechanical efficiency which are suitable for 800 meter running. Emphasis on sustained, progressive overload and short rest periods of the circuit training method resulted in improved anaerobic and aerobic capacities. Better pacing strategies and running mechanics were also detected, which are fundamental for achieving peak performance at the 800 m race. The findings emphasize the need to incorporate scientifically-based sport-specific training strategies to elicit neuromuscular adaptations and endurance responses in young athletes. Further investigation is warranted on the larger sample and different training intensities Customary to confirm and generalize these findings.